Proximity projection grating structured illumination microscopy - Chuang, Chin-Jung (2011)
Structured illumination has been employed in fluorescence microscopy to extend its lateral resolution. It has been demonstrated that a factor of 2 improvement can be achieved. In this thesis, we introduce a novel optical arrangement, which we call Proximity Projection Grating Structure Illumination Microscopy (PGSIM). Although the method is based on the original structured illumination, the present technique can further improve the lateral resolution of the microscope. The technique makes use of a fine grating held in close proximity to the sample, with a layer of high refractive index optical thin film sandwiched between the two. The fringe pattern thus projected onto the sample contains grating vectors substantially higher than those that are possible with the original structured illumination setup. The presence of these very high grating orders is the basis for the significant improvement in the system resolution.